PERANCANGAN ULANG MEJA KERJA ERGONOMIS PADA KANTOR ADMINISTRASI DI PT MCDERMOTT BATAM - Ryan, Ryan Arvina Yosua Nababan; Zetli, Sri (Computer Science and Industrial Engineering, 2026)
Administrative employees at PT McDermott Indonesia perform prolonged computer-based tasks, which increases the risk of musculoskeletal disorders due to the use of a non-ergonomic workstation. The existing desk is too low, the monitor position is misaligned with eye level, and the working posture tends to be forward-bending, leading to significant physical discomfort. This study aims to redesign an ergonomic workstation by utilizing anthropometric data and assessing postural risk using the Nordic Body Map (NBM) and Rapid Upper Limb Assessment (RULA) methods. Data were collected through field observations, interviews, documentation, NBM questionnaires, postural angle measurements, and body dimension measurements. The NBM assessment shows that all administrative employees fall into the high-risk category, with scores ranging from 78 to 81. The RULA analysis yields a final score of 6, indicating that immediate corrective action is required. Based on the anthropometric data, an ergonomic desk design is proposed with dimensions tailored to the majority of users, including adjustable height and optimized monitor placement. The redesigned workstation is expected to reduce musculoskeletal risks, improve comfort, and enhance productivity among administrative employees at PT McDermott Indonesia.